Contributions on the diet and distribution of Ocelot Leopardus pardalis (Linné 1758) in the high Andes of Ecuador - Nivelo-Villavicencio, Carlos Hernán (2019)
The Ocelot, Leopardus pardalis is a carnivore with wide distribution in South America. In Ecuador, most of the records come from lowland tropical forests and foothills of the Andes (<900 m at sea level), where this species has a variety of prey, particularly small mammals. However, in the high Andean regions, neither their occurrence nor their diet is known. On November 8, 2016 an adult male of L. pardalis was collected dead in the Usho locality, province of Cañar; the record is located in the high-Andean region in south of Ecuador at 2818 meters to sea level. During the evaluation of the specimen, several digested barbs were found and these were associated with the species of short-tailed porcupine, Coendou rufescens. This record shows that L. pardalis occurs at least seasonally in the high-Andean region of Ecuador; It also shows predation on the high-Andean species in their eating habits.